Oscillation of second order neutral dynamic equations with distributed delay - Qiaoshun Yang; Zhiting Xu; Ping Long (Electronic Journal of Qualitative Theory of Differential Equations, 2016)
In this paper, we establish new oscillation criteria for second order neutral dynamic equations with distributed delay by employing the generalized Riccati transformation. The obtained theorems essentially improve the oscillation results in the literature. And two examples are provided to illustrate to the versatility of our main results.